Long wavelength mid-infrared multi-gases spectroscopy using tunable single-mode slot waveguide quantum cascade laser - Jin, Yuhao (2023)
Single-mode tunable quantum cascade lasers (QCLs) are promising for high-resolution and highly sensitive trace gases sensing across the mid-infrared (MIR) region. We report on the development of a tunable single-mode slot waveguide QCL array in the long wavelength part of the MIR regime (>12 µm). This laser array exhibits a tuning range of around 12 cm−1, from 735.3 to 747.3 cm−1. Using this developed single-mode tunable QCL, we demonstrate individual gas sensing, yielding the detection limit of 940 ppb and 470 ppb for acetylene and o-xylene, respectively. To verify the potential of the developed QCL array in multi-species gas detection, laser absorption measurements of two mixed gases of acetylene and o-xylene were conducted, showing the absorption features of the corresponding gases agree well with the theoretical predictions.